دور صناديق الزكاة في علاج مشكلة الفقر -دراسة حالة صندوق الزكاة لولاية الوادي- - بن سعد نصر (University of Eloued جامعة الوادي, 2024)
لا تزال طرق معالجة الفقر مثار جدل بين الباحثين الاقتصاديين. نهدف من خلال هذه الدراسة تقييم مدى قدرة صندوق الزكاة لولاية الوادي في معالجة مشكلة الفقر في ولاية الوادي خلال الفترة (2004-2024). نستخدم المنهج الوصفي التحليلي من أجل تقييم دور صندوق الزكاة في التقليل من معدلات الفقر. تثبت النتائج المتحصل عليها، بأنه على الرغم من الدور المتنامي لصندوق الزكاة في الفترة الأولى، غير أنه بدأ هذا الدور في الانخفاض في الفترة الأخيرة وهذا راجع لقلة في حصيلة الزكاة. The methods of addressing poverty remain a topic of debate among economic researchers. Through this study, we aim to uncover the extent to which the Zakat Fund in Oued Province can address the problem of poverty during the period from 2004 to 2024. We use a descriptive-analytical approach to evaluate the role of the Zakat Fund in reducing poverty rates. The obtained results demonstrate that, despite the growing role of the Zakat Fund in the initial period, this role has started to decline in recent times due to the decreased collection of Zakat.
Keywords: الفقر، زكاة، صندوق الزكاة.; Poverty; Zakat; Zakat Box